2013
DOI: 10.1128/iai.01037-12
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Requires the ESCRT Protein Vps23 for Iron Acquisition from Heme, for Capsule Formation, and for Virulence

Abstract: Iron availability is a key regulator of virulence factor elaboration in Cryptococcus neoformans, the causative agent of fungal meningoencephalitis in HIV/AIDS patients. In addition, iron is an essential nutrient for pathogen proliferation in mammalian hosts but little is known about the mechanisms of iron sensing and uptake in fungal pathogens that attack humans. In this study, we mutagenized C. neoformans by Agrobacterium-mediated T-DNA insertion and screened for mutants with reduced growth on heme as the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 75 publications
2
125
0
Order By: Relevance
“…In this study, we demonstrated a previously unknown function of flippases in physiological and pathogenic secretion-related events used by C. neoformans. To the best of our knowledge, cryptococcal regulators of secretion described so far include the products of the SEC (51,58,64) and CAP genes (65-70), Golgi reassembly and stacking protein (30), protein kinase A (71), vacuolar Ca 2ϩ transporters (35,59), and the vacuolar protein Vps23 (72). Mutants with altered expression of the genes coding for each of these secretory regulators are hypovirulent or avirulent in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated a previously unknown function of flippases in physiological and pathogenic secretion-related events used by C. neoformans. To the best of our knowledge, cryptococcal regulators of secretion described so far include the products of the SEC (51,58,64) and CAP genes (65-70), Golgi reassembly and stacking protein (30), protein kinase A (71), vacuolar Ca 2ϩ transporters (35,59), and the vacuolar protein Vps23 (72). Mutants with altered expression of the genes coding for each of these secretory regulators are hypovirulent or avirulent in mice.…”
Section: Discussionmentioning
confidence: 99%
“…5C). This insertion mutant was obtained in a previously reported screen for mutants with reduced growth on hemin, and it had a more obvious growth defect than with the fre2⌬ strain (35). Interestingly, the fre2 insertion mutant was generated in the background of a cfo1⌬ mutant that lacks the ferroxidase of the high-affinity iron uptake system (35).…”
Section: Ferric and Cupric Reductase Activities Of Fre Deletion Strainsmentioning
confidence: 99%
“…This insertion mutant was obtained in a previously reported screen for mutants with reduced growth on hemin, and it had a more obvious growth defect than with the fre2⌬ strain (35). Interestingly, the fre2 insertion mutant was generated in the background of a cfo1⌬ mutant that lacks the ferroxidase of the high-affinity iron uptake system (35). Thus, the difference in the growth defects between the fre2 T-DNA insertion and deletion mutants indicates that the high-affinity iron uptake system, along with Fre2, makes a contribution to iron acquisition from hemin.…”
Section: Ferric and Cupric Reductase Activities Of Fre Deletion Strainsmentioning
confidence: 99%
“…Interestingly, Vps23 has been shown to be involved in iron acquisition, capsule formation, and virulence. However, these functions may be explained by the role of Vps23 in endocytosis, and its contribution, like other ESCRT factors, in Rim101 processing in C. neoformans has not been demonstrated yet (106). Many of the genes involved in cell wall biosynthesis and remodeling are regulated by Rim101 in C. neoformans (CHS4, CHS5, CHS6, CHS8, SKN1, FKS1, KRE6, CDA3, CHI22, and AGS1) (107).…”
Section: Ph Signaling and Cryptococcus Neoformans Virulencementioning
confidence: 99%